A novel practical algorithm for strong and weak synonyms extraction with simple equality operation of web operational machine translation systems results. Issue 3 (27th September 2022) - Mosbah, Mawloud
In this paper, we address synonyms extraction through a simple algorithm based on equality operation of translated segments generated by four free of charge web machine translation systems namely: Google Translate, Promt, Babylon and Bing . The synonyms are classified into two kinds: strong synonyms with different vocabularies, and weak synonyms with the same vocabularies and different part of speech nature. The obtained results, using a dataset of ten theses abstracts, published into the web, seem to be very promising. Moreover, according to this study, it is advised that weak synonyms should receive more attention especially into synonyms substitution for machine translation evaluation.